2011
DOI: 10.3111/13696998.2011.604369
|View full text |Cite
|
Sign up to set email alerts
|

Pain, health related quality of life and healthcare resource utilization in Spain

Abstract: The societal burden of severe and frequent pain in Spain is substantial. Although not reported on before, at a national level, the deficit impact of the experience of pain far outweighs the contribution of more traditional explanations of HRQoL deficits as well as being the primary factor associated with increased provider visits, emergency room visits and hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
1
20
1
2
Order By: Relevance
“…Although these findings contrast other studies [14,15], the differences observed may be due to differences in the number of levels used to classify smoking patterns. [14,15]. In our study, low risk drinkers had the best health and non-drinkers reported the poorest health in all three cohorts, supporting finding from other EQ-5D research [44].…”
Section: Discussioncontrasting
confidence: 56%
“…Although these findings contrast other studies [14,15], the differences observed may be due to differences in the number of levels used to classify smoking patterns. [14,15]. In our study, low risk drinkers had the best health and non-drinkers reported the poorest health in all three cohorts, supporting finding from other EQ-5D research [44].…”
Section: Discussioncontrasting
confidence: 56%
“…More recently, Fernández-de-las-Peñ as et al 16 report on estimates from the 2006 Spanish National Health Survey to assess the prevalence of neck and low back pain with occupation and income as part of a profile of socio-economic status. Two recent companion Spanish studies have reported on the overall prevalence and correlates of pain 17 and the impact of pain on health-related quality-of-life and healthcare resource utilization 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study covering five EU countries-the UK, France, Spain, Italy, and Germany-found that pain severity and frequency had the strongest association with HRQoL, traditional provider, visits, and hospitalizations of all variables considered in a comprehensive multivariate modeling framework 12 . The NHWS has also supported a separate analysis for Spain to assess the impact of pain severity and frequency on HRQoL, health status, and healthcare resource utilization 13 .…”
Section: Introductionmentioning
confidence: 99%